Given:
![\begin{gathered} f(3)=-2 \\ f^{^(\prime)}(3)=-8 \\ g(x)=(1)/(f(x)) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/mfhp590d92n5r2qd4uld6i2do5ox111pwm.png)
Solution:
If f(3)=-2, then f'(-2)=3
Hence, the points are (-2,3). These points will be on the graph of the inverse function to f(x).
The function g(x) is as
![\begin{gathered} g(x)=y \\ =(1)/(f(x)) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/nrsjzuosrot0eq828b08jvw2sqqpmxeawi.png)
Now, the tangent line slop will be as
![\begin{gathered} f(-2)=\frac{1}{f^{^(\prime)}(3)} \\ =(1)/(-8) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/y50s9bza3r7aai19oedj5hmm1eap7s0bkl.png)
The equation of the tangent line will be as
![\begin{gathered} y-3=(1)/(-8)(x-(-2)) \\ y-3=(1)/(-8)(x+2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/lcnprns5af8ycxiqrupjre2plhfmsza8gt.png)
Answer:
Hence, the tangent line equation is as
![y=(1)/(-8)(x+2)+3](https://img.qammunity.org/2023/formulas/mathematics/college/cm5cpc9733jnrorfqu8vifjel9npy2zph7.png)